#BlackGirlMagic: Using multiple data sources to learn about Black adolescent girls' identities, intersectionality, and media socialization. (5th December 2021) - Rogers, Leoandra Onnie; Butler Barnes, Sheretta; Sahaguian, Lily; Padilla, Dayanara; Minor, Imani
Abstract: A robust literature shows that (parental) ethnic‐racial socialization (ERS) influences Black youths' identity development. Other sources of socialization, like media, are acknowledged but scarcely represented in empirical studies. In this study, we conceptualize #BlackGirlMagic (#BGM), a social media hashtag, as a media‐based ERS message and examine its association with identity outcomes among Black adolescent girls ( N = 63; Mage = 16.17). Analyzing qualitative and quantitative data, we show that Black girls interpret #BGM as a message of: (a) Affirmation ; (b) Societal Oppression ; (c) Collectiveness ; and (d) Being Seen/Heard . Furthermore, girls' interpretations of #BGM were significantly associated with racial identity measures and the content of their racial and gender identity interviews. Implications for socialization and identity research and the study of Black girls' development are discussed.